Tempo médio de saída e desigualdades isoperimétricas para subvariedades mínimas de N x R - Chaves, Francisco Pereira (2011)
It establishes isoperimetric inequalities and exit mean time estimates for minimal submanifolds of N x R, where N is a complete Riemannian manifold with sectional curvature non-positive. It proves isoperimetric inequalities for submanifolds with tamed second fundamental form in Hadamard spaces with bounded sectional curvature.